2010
DOI: 10.1002/dvdy.22373
|View full text |Cite
|
Sign up to set email alerts
|

Gata2 is required for the development of inner ear semicircular ducts and the surrounding perilymphatic space

Abstract: *Gata2 has essential roles in the development of many organs. During mouse inner ear morphogenesis, it is expressed in otic vesicle and the surrounding periotic mesenchyme from early on, but no defects in the ear development of Gata2 null mice have been observed before lethality at embryonic day (E) 10.5. Here, we used conditional gene targeting to reveal the role of Gata2 at later stages of inner ear development. We show that Gata2 is critically required from E14.5-E15.5 onward for vestibular morphogenesis. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 62 publications
0
57
0
1
Order By: Relevance
“…However, neither heterozygous nor homozygous knock-out mice were reported with any overt defect of the vasculature, which may suggest a level of functional redundancy of Gata2 to other Gata family members in these tissues in the mouse. We also note the described function of Gata2 in vestibular morphogenesis and growth of the semicircular canals 15 , the relationship of these findings with the development of sensorineural deafness in three of the 13 mutation carriers requires further investigation.…”
mentioning
confidence: 80%
“…However, neither heterozygous nor homozygous knock-out mice were reported with any overt defect of the vasculature, which may suggest a level of functional redundancy of Gata2 to other Gata family members in these tissues in the mouse. We also note the described function of Gata2 in vestibular morphogenesis and growth of the semicircular canals 15 , the relationship of these findings with the development of sensorineural deafness in three of the 13 mutation carriers requires further investigation.…”
mentioning
confidence: 80%
“…(18) GATA2 is also important in vestibular morphogenesis and growth of semicircular canals. (19) This could explain the sensorineural deafness in Emberger syndrome. But the reason for its presence in only some patients is not known.…”
Section: Emberger Syndromementioning
confidence: 98%
“…In one study, it has been suggested that N-terminal frameshift mutations or larger deletions of GATA2 are more likely to cause lymphedema [23]; however, this association could not be confirmed in other patient cohorts [6]. Congenital deafness is presumed to result from failure of generation of the perilymphatic space surrounding the semicircular ducts in inner ear [29].…”
Section: Emberger Syndromementioning
confidence: 99%